Cover Fuel Cells 3/2018. Issue 3 (13th June 2018) - Unknown
Abstract : This Special Issue is related to the 7 th International Conference on Fundamentals & Development of Fuel Cells (FDFC 2017), held January 31 to February 02, 2017, in Stuttgart, Germany associated to the German Aerospace Centre (DLR), with Prof. A. Friedrich as Conference Chair. This biennial Conference covered energy, power, energy efficiency, hybrid vehicles, fuel cells and hydrogen storage matters. The Special Issue consists of manuscripts, pre‐selected by the Guest Editors from the submitted extended abstracts.